THU0667 Disease, work and personal related factors associated with presenteeism in patients with rheumatoid arthritis: results from the national rheumatoid arthritis society survey (NRAS). (12th June 2018) - Verstappen, S.; Gignac, M.; Lunt, L.; Beaton, D.; Bosworth, A.; Bezzant, M.; Walker-Bone, K.
Abstract : Background: At-work productivity loss (i.e. presenteeism) is a major problem for patients with rheumatoid arthritis (RA) and employers and could be a marker of long-term absenteeism. To develop interventions to prevent presenteeism, a better understanding of which factors are associated with presenteeism is needed. Objectives: To assess the association between disease and work related factors with presenteeism. Methods: A large survey about employment amongst patients with RA was conducted in the UK using an online platform and inviting NRAS members and non-members to participate. Patients completed the multi-item Workplace Activity Limitation Scale (WALS; range 0–36 worst score), a measure of presenteeism. Other job related questions included: occupation (NS-SEC coding), job demand questions, help from colleagues (categorised into: always/often, sometimes, rarely/never) and a patient acceptable state questionnaire about work (PASS). Patients also completed the disease specific RAID questionnaire (score 0–10=worst score). Univariable and multivariable linear regression analyses were performed to assess the association between the disease and job related factors and presenteeism, adjusting for age and gender. Results: 891 respondents were in paid work at the time of the survey (51.5% working for others, 33.1% self-employed and 15.4% on temporary sick leave). The majority of participants were women (91.5%) and 4.9% were aged 16–30, 69.2% 31–54% and 25.8% aged 55–74 years. Over half (51.5%) had a higher managerial, administrative or professional occupations, 33.1% an intermediate occupation, and 15.4% a routine/manual occupation. Mean (SD) RAID score was 5.2 (2.2). 58.2% rated their current job performance somewhat/much worse than before the onset of their arthritis. In univariable regression analyses greater disease activity, less control, lower support from colleagues and being in a unacceptable disease state (PASS) were associated with higher levels of presenteeism. In multivariable analysis, disease activity, ability to influence work and a unacceptable disease state remained statistically significantly associated with presenteeism. Conclusions: In this large national survey in patients with RA we found that not only disease activity, but also having control, especially the flexibility to influence work and take breaks when needed, were associated with levels of presenteeism. Preventing presenteeism should therefore be aimed at managing the disease, but also toward adapting work circumstances and finding the right balance between work requirements and personal needs. Disclosure of Interest: None declared